2020
DOI: 10.1016/j.cell.2020.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stimulation of Visual Cortex Produces Form Vision in Sighted and Blind Humans

Abstract: Highlights d Visual cortical prosthetic stimulation paradigms were examined d Letters or other shapes were traced on the surface of cortex with electrical current d Static stimulation was unable to produce letter percepts in participants d Dynamic current steering evoked percepts of letter forms by blind and sighted participants

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
189
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(197 citation statements)
references
References 54 publications
5
189
0
3
Order By: Relevance
“…Importantly, the existence of cortical responses in the de-afferented visual cortex, as demonstrated in the present study, suggests that the LPZ is still to some degree operational. This finding is consequently in support of approaches restoring visual input to the cortex (Aguirre, 2017;Beauchamp et al, 2020;Chuang et al, 2014;Jutley et al, 2017;Sena and Lindsley, 2017;Venugopalan et al, 2016). High cost and limited availability makes the utility of MRI in routine clinical ophthalmological examinations less plausible.…”
Section: Clinical Relevance In the Context Of Emerging Therapeutic Insupporting
confidence: 54%
“…Importantly, the existence of cortical responses in the de-afferented visual cortex, as demonstrated in the present study, suggests that the LPZ is still to some degree operational. This finding is consequently in support of approaches restoring visual input to the cortex (Aguirre, 2017;Beauchamp et al, 2020;Chuang et al, 2014;Jutley et al, 2017;Sena and Lindsley, 2017;Venugopalan et al, 2016). High cost and limited availability makes the utility of MRI in routine clinical ophthalmological examinations less plausible.…”
Section: Clinical Relevance In the Context Of Emerging Therapeutic Insupporting
confidence: 54%
“…These results provide promising implications on the cortical prosthesis, which enables the reconstruction of visual experience, making use of intact neural tissue and preserved retinotopic organization. [60][61][62] Although many previous studies reported tactile-or auditoryevoked V1 responses in blind patients, [63][64][65][66][67][68] they did not assess the task dependency of responses. JMD patients have preserved visual fields, enabling us to assess the impact on intact feedforward signals.…”
Section: Report Discussionmentioning
confidence: 99%
“…In addition, these large electrodes interacted with relatively large volumes of cortex (∼1 cm 3 ), resulting in very low spatial resolution of the perceived phosphenes (Christie et al, 2016;Niketeghad et al, 2019). These later findings have recently been confirmed by Beauchamp et al (2020), who implanted two different types of electrodes on the surface of the visual cortex of two blind individuals and found that when multiple electrodes were stimulated simultaneously, phosphenes fused into larger formless perceptions, making shape recognition impossible.…”
Section: Electrodes That Interact With the Brain In The Blind: Generamentioning
confidence: 84%